Patient referral from primary care to psychological therapy services: a cohort study. (12th December 2019) - Jonker, Leon; Thwaites, Richard; Fisher, Stacey J
Abstract: Background: Improving Access to Psychological Therapy (IAPT) services in England offer psychological therapy for patients with mental health issues such as depression and anxiety disorders. Objective: How are primary care patients referred to IAPT, to what degree does this correlate with subsequent attendance, and how is the referral process perceived by patients? Methods: Retrospective analysis of medical records covering June 2018–June 2019 in seven general practices servicing 96 000 patients, to identify and survey patients with anxiety and/or depression. Results: Records of 6545 patients were appraised; 2612 patients were deemed suitable for IAPT intervention by the GP. Of those, 1424 (55%) attended at least one IAPT appointment whereas 1188 (45%) did not. These 'attender' and 'non-attender' cohorts did not differ in age, gender or level of deprivation; neither did GP advice to self-refer rather than making a direct GP referral influence the attendance rate. The most common reasons for IAPT non-attendance include symptom improvement (22%), lack of belief in psychotherapy effectiveness (16%) or a patient feeling too unwell to either refer themselves or attend (12%). Conclusions: Neither certain age or gender, nor the mode of patient referral to IAPT is associated with eventual attendance. Future research is indicated to identify in more detail if any specific mental health conditions are more likely to lead to non-attendance. Furthermore, there may be scope for a targeted approach for subgroups of patients, e.g. those who indicate they are feeling mentally too unwell, to enable them to attend IAPT screening and therapy appointments.